2006
DOI: 10.1007/s10460-004-5862-y
|View full text |Cite
|
Sign up to set email alerts
|

Importing Corn, Exporting Labor: The Neoliberal Corn Regime, GMOs, and the Erosion of Mexican Biodiversity

Abstract: When genetically modified (GM) imported corn was found growing in Oaxaca and the Tehuacán Valley of Puebla, Mexico (2000, it intensified the debate between activists, academics, and government officials about the effects of trade liberalization on Mexican corn farmers and maize biodiversity. In order to understand the challenges faced by corn farmers and in situ diversity, it is important to contextualize GM corn within the recent neoliberal corn regime and its regional manifestations. This essay offers a case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(31 citation statements)
references
References 9 publications
1
27
0
3
Order By: Relevance
“…The iterative searches showed that while some papers of relevance to the topic (such as [28][29][30][31][32][33][34][35][36][37]) were indeed not captured in the search, these were sufficiently few not to challenge the overall findings presented here and did not address other topics than those also addressed in the reviewed literature. The iterative searches also showed that in particular, literature addressing cultural heritage impacts of GM crops in agriculture fell outside the search.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The iterative searches showed that while some papers of relevance to the topic (such as [28][29][30][31][32][33][34][35][36][37]) were indeed not captured in the search, these were sufficiently few not to challenge the overall findings presented here and did not address other topics than those also addressed in the reviewed literature. The iterative searches also showed that in particular, literature addressing cultural heritage impacts of GM crops in agriculture fell outside the search.…”
Section: Methodsmentioning
confidence: 99%
“…The iterative searches also showed that in particular, literature addressing cultural heritage impacts of GM crops in agriculture fell outside the search. Examples of relevant studies are [32][33][34][35][36][37]. However, even taking into account the additional papers found in the iterative searches, such studies remain few in comparison with the other impact groups (see Section 3.2).…”
Section: Methodsmentioning
confidence: 99%
“…Small-scale studies on socioeconomic and environmental changes have shown that maize farmers continue planting maize for socioeconomic and cultural reasons and how they have adapted to this economic context [4,45]. However, we believe that there are other crops such as beans that have been affected by those policies.…”
Section: Discussionmentioning
confidence: 95%
“…Neoliberalism is characterized by strong market integration and trade liberalization between countries and a change in the role of the government as an economic agent [3]. International free-trade agreements such as NAFTA (North American Free Trade Agreement) are instances of such neoliberal policies [4]. NAFTA created a free-trade zone among Canada, the USA, and Mexico.…”
Section: Introductionmentioning
confidence: 99%
“…More recent observations of international migrants from maize-growing regions in the state of Puebla (Fitting 2006(Fitting , 2004 suggest that, while migration may initially lead to reinvestment in traditional maize production in the form of remittances or the investments of returned migrants, only older migrants are likely to return to their communities and establish their own milpas. Younger migrants, in contrast, are less likely to have worked for a significant period of time in agriculture before migrating, and are also less likely to learn seed selection practices or common local-language agricultural terms describing maize cultivation when they return.…”
mentioning
confidence: 99%